The well: the deep VS the obvious - Kapustin, Petr (project baikal, 2022)
An ancient belief, dating back to Pliny and Aristotle, claims: if you look from the bottom of a deep well, you can see the stars during the day. Numerous empirical contradictions are worthless, since it is obviously not about the retinal effect. The ancient evidence of the well as an optical clairvoyance device hints at its place in the mythopoetics of inhabited space, and this role is not merely reduced to water delivery. The article attempts to “capture” in a topical but generalized discourse the mythopoetics of wells as they are known in the history of architecture and civilization.